The Influence of Marketing 5.0 and Creating Share Value on Wound Care Quality and Purchased Intention among Wound Care Professional - Gitarja, Widasari Sri; Hariyati, Rr. Tutik Sri (AIBPM Publisher, 2023)
This literature review examines the Influence of Marketing 5.0 and Creating Share Value on Wound Care Quality and Purchase Intention among Wound Care Professionals. As contemporary marketing practices evolve, the emergence of Marketing 5.0 signifies a shift towards holistic and customer-centric strategies, emphasising the significance of meaningful interactions and value co-creation. Simultaneously, Creating Share Value underscores the role of businesses in addressing societal challenges alongside profit generation. This literature review reveals that Marketing 5.0 strategies promise to enhance the quality of wound care services through personalised communication, enhanced patient engagement, and technology-enabled solutions. Creating Share Value initiatives establishes a sense of purpose and collaboration among wound care professionals, ultimately contributing to improved patient care and organisational success. The literature review of these marketing strategies contributes to understanding contemporary marketing concepts in the healthcare context, particularly wound care.